Evaluation of Islamic Education Policy in Indonesia: Challenges and Opportunities in the Era of Information Disruption and Post-Truth - Irfan, Agus; Amri, M. Saeful; Munkhakim, M. Ali (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This study examines the evaluation of Islamic education policy in Indonesia in the context of the information disruption and post-truth era. Rapid technological advancements and the widespread influence of digital media have significantly transformed educational paradigms, creating both challenges and opportunities for Islamic education. The research explores how existing policies respond to issues such as misinformation, moral degradation, and the shifting learning culture among students. Using a qualitative approach and policy analysis framework, this paper identifies gaps in implementation, particularly in digital literacy, teacher competence, and curriculum relevance. The findings suggest that Islamic education policy must be adaptive, inclusive, and innovative—integrating technological literacy with moral and spiritual values to maintain relevance in the digital age. Strengthening collaboration among stakeholders, updating curriculum content, and promoting critical thinking are key strategies to ensure that Islamic education contributes effectively to character building and national development in the post-truth era.